1992
DOI: 10.1007/bf00756818
|View full text |Cite
|
Sign up to set email alerts
|

Normal housing: A key element of a supported housing approach for people with psychiatric disabilities

Abstract: This article summarizes current thinking in the field about the types of housing environments which are most relevant both to the overall goal of community integration, and to the variety of specific support needs of individuals with psychiatric disabilities. Within the context of a "supported housing" approach, which focuses on maximizing consumers choices and preferences, using integrated regular housing stock, and making a full array of community supports available, the authors propose a number of specific … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
28
0

Year Published

1997
1997
2014
2014

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(28 citation statements)
references
References 6 publications
0
28
0
Order By: Relevance
“…Taken together, these characteristics of the Continuum of Care result in dissatisfaction and frustration with services that undermine consumers' autonomy, and is, in part, responsible for the birth of consumer movements that called for an increase in choice and control over treatment and after-care options for mentally ill individuals (Chamberlin & Rogers, 1990;Garfinkel & Dorian, 2000;Hogan & Carling, 1992).…”
Section: Comparisons Of Continuum Of Care and Housing Firstmentioning
confidence: 97%
“…Taken together, these characteristics of the Continuum of Care result in dissatisfaction and frustration with services that undermine consumers' autonomy, and is, in part, responsible for the birth of consumer movements that called for an increase in choice and control over treatment and after-care options for mentally ill individuals (Chamberlin & Rogers, 1990;Garfinkel & Dorian, 2000;Hogan & Carling, 1992).…”
Section: Comparisons Of Continuum Of Care and Housing Firstmentioning
confidence: 97%
“…With this approach: (a) consumers/survivors do not have choice over where or with whom they live; (b) they are often concentrated in one setting, thus inhibiting rather than promoting broader community integration; and (c) they may be forced to move into a less-supportive residential setting when they show improvement, thus disrupting relationships that they have developed with living companions and staff (Hogan & Carling, 1992;Ridgway & Zipple, 1990). Such forced relocation can have the effect of disassembling social networks, which other research has shown to be centrally important to fostering the adaptation of psychiatric consumers/survivors to life in the community (Hall & Nelson, 1996;Nelson, Hall, Squire, & Walsh, 1992).…”
mentioning
confidence: 99%
“…In this context, Paul Carling and his colleagues promoted the concept of "supported housing" (which had already taken root in the fields of developmental and physical disabilities under the rubric of "independent living") to the field of mental health as a response to deficiencies in the available alternatives (Carling, 1995;Hogan & Carling, 1992;Ridgway & Zipple, 1990). There are three key principles of supported housing:…”
mentioning
confidence: 99%
“…Supported housing-that is, independent housing coupled with the provision of community-based mental health services-has been considered the housing approach most conducive to consumer empowerment and community integration (Blanch, Carling, & Ridgway, 1988;Carling, 1992). Proponents of supported housing maintain that persons with psychiatric disabilities can assume roles and lifestyles as regular community members in a normal, integrated housing environment, when they are given flexible and individualized mental health support services.…”
Section: Introductionmentioning
confidence: 99%